(untitled) (Boulder, 2001)
When considering the nature of environmental problems, many scholars and practitioners assume that - while there may be disagreement about solutions - we know what the problems are. In contrast, the authors of this volume investigate the framing of both problems and solutions to clarify the particular political dynamics and preferences that they reflect and legitimate. They test their analytical tools on the real world of internationa environmental politics, combining theory with empirical research. All of the chapters raise theoretical questions at the core of research and policymaking that values social equity and environmental health. In combination, they tell a cohesive, substantive story about the IPE of the environment at the beginning of the third millennium.
Keywords: Environmental policy,Economic development,International economic relations; Economic aspects,Economic aspects